The Impact of Multicultural Identities in Classrooms on the Practice of English Language Teachers: A Case Study of Native and Non-Native English Language Teachers - EMARA, TAREK MAHMOUD IBRAHIM (2018)
Over the past years, many debates have been raised over certain variables that have great influences on teaching English to second language learners. Of these, cultural diverse identities stand distinguished in the queue. To hit the main purpose of the current study, a qualitative method is used to examine to what extent the teaching of English language teachers (ELTs) is influenced by their awareness of multicultural identities in classrooms, especially when they have limited conceptions of the issue, tackling it in terms of certain socio-cultural theories. Two methodological tools have been employed: a classroom observation and an interview with each of the participant ELT. The present study tackles four major points: a) How do the ELTs, native and non-native, perceive multicultural identities in their classrooms? b) How ELTs’ performances are affected, positively or negatively, by this situation? c) How do the ELTs make use of their potentials to handle such a situation? And d) What are the relevant and effective strategies that should be adopted to promote the ELTs’ performances when teaching in such classrooms?